The project “GPTheatre: Generative AI for Humanities” (Itinera, 2025)
This issue originates from a one-year interdisciplinary project entitled GPTheatre, funded by the University of Milan between July 2024 and June 2025 as part of the “My First Seed” grant scheme. The project, led by Alice Barale (philosopher, PI), Luca Daino (literature scholar), and Matteo Zignani (computer scientist), aimed to investigate interaction with generative artificial intelligence, and in particular the peculiar form of dialogue that human beings are increasingly establishing with this technology. To do so, it intended to bring some of these dialogues onto the stage, as theatrical dialogues.As the context in which to undertake this experiment, GPTheatre chose the university: several professors from the University of Milan would interact with ChatGPT, and from these dialogues — with the help of the AI itself — the performance would emerge. The staged reading ViaggIAccademici was presented in Milan at Teatro degli Angeli on May 8 2025, and in Verona at Spazio Vitale on November 16 of the same year (and it will return to Milan in February 2026). The story offered to the audience is that of a peculiar student who undertakes a “journey” through various classrooms of his university in search of a thesis advisor (and perhaps, at least for his human interlocutors, also in search of the meaning of their own research).